Adult exposure to ocean acidification and warming remains beneficial for oyster larvae following starvation. (12th April 2021) - Gibbs, Mitchell C; Parker, Laura M; Scanes, Elliot; Byrne, Maria; O'Connor, Wayne A; Ross, Pauline M
Abstract: Climate change is expected to warm and acidify oceans and alter the phenology of phytoplankton, creating a mismatch between larvae and their food. Transgenerational plasticity (TGP) may allow marine species to acclimate to climate change; however, it is expected that this may come with elevated energetic demands. This study used the oysters, Saccostrea glomerata and Crassostrea gigas, to test the effects of adult parental exposure to elevated p CO2 and temperature on larvae during starvation and recovery. It was anticipated that beneficial effects of TGP will be limited when larvae oyster are starved. Transgenerational responses and lipid reserves of larvae were measured for 2 weeks. Larvae of C. gigas and S. glomerata from parents exposed to elevated p CO2 had greater survival when exposed to elevated CO2, but this differed between species and temperature. For S. glomerata, survival of larvae was greatest when the conditions experienced by larvae matched the condition of their parents. For C. gigas, survival of larvae was greater when parents and larvae were exposed to elevated p CO2 . Larvae of both species used lipids when starved. The total lipid content was dependent on parental exposure and temperature. Against expectations, the beneficial TGP responses of larvae remained, despite starvation.